(untitled) (Journal of Parents and Teachers, 2014)
This article analyses the relationship between spectators and horror. Through empathy, the spectator puts in the characters’ shoes and he is able to experience suffering, compassion and mercy. Modern psychology explains that horror cinema produces shock and fear. Fear activates our most primitive instincts to be aware and ready to flee or fight. Horror film directors use some strategies to provoke this fear, such as the recreation of a suitable atmosphere and the relationship the spectator establishes with the characters.